THE EFFECT OF CONTEXTUAL LEARNING TO IMPROVE 12TH GRADE STUDENTS' COGNITIVE ABILITY ON ELECTROLYSIS CONCEPT - Studianah, Wido (Jurnal Pengajaran MIPA, 2019)
The research entitled "The Implication Of Contextual Learning To Improve Students 12 Science's Cognitive Aspect On Electrolysis Concept" aims to obtain an overview of the cognitive aspects of students that are applied through contextual learning on electrolysis cell material. In addition, student participation was also studied during learning. To find out the increase in cognitive abilities of students conducted research with the method used in the study was the quasi-experimental method of pretest-posttest design. The research subjects consisted of 46 students of class XII IPA. The instruments used were evaluation sheets (pretest and posttest), student worksheets (LKS), learning sheets, observation sheets and questionnaires. The results showed that the use of contextual learning models could improve the cognitive abilities of students with normalized gain of 55.37% (sufficient category). Student participation during learning is almost half (40.22%) students ask teachers or group friends, almost half (39.13%) of students answer questions from teachers or group friends and most (90.94%) students are active in groups. The questionnaire results show that students respond well to contextual learning using practical methods. This shows that students tend to be more interested in learning that raises the facts they find in daily life. ABSTRAKPenelitian yang berjudul ? Penerapan Pembelajaran Kontekstual Untuk Meningkatkan Aspek Kognitif Siswa Kelas XII IPA  Pada Konsep Elektrolisis ? ini bertujuan untuk memperoleh gambaran tentang aspek kognitif siswa yang diterapkan melalui pembelajaran kontekstual pada materi sel elektrolisis. Selain itu dikaji pula partisipasi siswa selama pembelajaran. Untuk mengetahui peningkatan kemampuan kognitif siswa dilakukan penelitian dengan metode yang digunakan dalam penelitian adalah metode kuasi eksperimen desain pretest-postest. Subyek penelitian terdiri dari 46 orang siswa kelas XII IPA. Instrumen yang digunakan berupa lembar evaluasi (pretest dan postest), lembar kerja siswa (LKS), lembar pembelajaran, lembar observasi dan angket. Hasil penelitian menunjukkan bahwa penggunaan model pembelajaran kontekstual dapat meningkatkan kemampuan kognitif siswa dengan normalisasi gain 55,37 % (kategori cukup). Partisipasi siswa selama pembelajaran hampir setengahnya (40,22%) siswa bertanya kepada guru atau kepada teman sekelompok, hampir setengahnya (39,13%) siswa menjawab pertanyaan guru atau teman sekelompoknya dan sebagian besar (90,94%) siswa aktif dalam kelompok. Hasil angket menunjukkan bahwa siswa merespon dengan baik pada pembelajaran kontekstual dengan menggunakan metode praktikum, Hal ini menunjukkan bahwa siswa cenderung lebih tertarik dengan pembelajaran yang mengangkat fakta-fakta yang mereka temukan dalam kehidupan sehari-hari. Keywords : Contextual learning, cognitive, electrolysis